2015
DOI: 10.4324/9781315850863
|View full text |Cite
|
Sign up to set email alerts
|

Emotions in Conflict

Abstract: Routledge Studies in Political Psychology was developed to publish books representing the widest range of theoretical, methodological and epistemological approaches in political psychology. The series is intended to expand awareness of the creative application of psychological theory within the domain of politics and foster deeper appreciation of the psychological roots of political behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 394 publications
(710 reference statements)
1
42
0
1
Order By: Relevance
“…Surprisingly, ethnoreligious affiliation of the target did not matter for this emotion, and individuals exposed to severe trauma expressed less fear. The expression of fear entails an estimation of a threat to be greater than one’s own coping ability (Halperin, 2015; Lazarus & Folkman, 1984). Expressing fear thus involves an attribution of relative weakness and vulnerability to the self, in addition to the perception of the target as a threat.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, ethnoreligious affiliation of the target did not matter for this emotion, and individuals exposed to severe trauma expressed less fear. The expression of fear entails an estimation of a threat to be greater than one’s own coping ability (Halperin, 2015; Lazarus & Folkman, 1984). Expressing fear thus involves an attribution of relative weakness and vulnerability to the self, in addition to the perception of the target as a threat.…”
Section: Discussionmentioning
confidence: 99%
“…While the relation between empathy-related processes and prosocial behavior for needy others has been studied for decades, there is less research on empathy-related processes in interpersonal conflict. This is surprising, as emotions in general and empathy in particular are increasingly being recognized as crucial factors in determining the course of conflicts (Halpeirn, 2015). A first correlational study that used questionnaire-based measures in adolescents observed that dispositional empathy, encompassing experience sharing, sympathy, and empathic distress, was related to more successful interpersonal conflict management strategies, such as positive problem solving (De Wied, Branje, & Meeus, 2007).…”
Section: The Role Of Empathy Compassion and Empathic Distress In Inmentioning
confidence: 99%
“…With over 230 million deaths due to violent conflict in the 20th century (Leitenberg, 2006), intergroup conflict is one of the greatest problems that our society is currently facing (Cohen & Insko, 2008). It is increasingly being recognized that in addition to disagreements about tangible issues, such as resources or socioeconomic conditions, emotions play a key role in conflicts (Halperin, 2015). Among emotional processes, empathy in general is often considered an important factor in promoting cooperation between interdependent individuals (de Waal, 2008) and good intergroup relations (Batson & Ahmad, 2009; Dovidio et al, 2010; Stephan & Finlay, 1999).…”
mentioning
confidence: 99%
“…It confirms longstanding observations by a number of social scientists and historians who suggest that remembrance of the distant Jewish past, and especially the Holocaust experience as actively propagated and fostered in Israel, feeds into Israeli citizens' fear of Arabs. 90 It would be surprising if similar results failed to hold for American Jews as well. To reverse Somers' formulation, we need to look not only at "the embeddedness of identity in overlapping networks of relations that shift over time and space," but also the embeddedness of networks of social relations in narrative-identities and their often-powerful political ramifications.…”
Section: Resultsmentioning
confidence: 98%